2000
DOI: 10.1021/om0004951
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization, and Reactivity of the Stable Indium Trihydride Complex [InH3{CN(Mes)C2H2N(Mes)}]

Abstract: Reaction of either LiInH 4 or [InH 3 (NMe 3 )] with the Arduengo-type carbene :CN(Mes)-C 2 H 2 N(Mes), Mes ) C 6 H 2 Me 3 -2,4,6, affords the indium trihydride complex [InH 3 {CN(Mes)-C 2 H 2 N(Mes)}]. This compound displays a remarkable thermal stability (dec 115 °C). In solution the products of decomposition depend on the solvent used. In toluene decomposition results in liberation of the free carbene and deposition of indium metal, and in tetrahydrofuran in the presence of indium metal hydrogen transfer occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
59
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 21 publications
(50 reference statements)
6
59
0
Order By: Relevance
“…There remains significant debate around the stability of In and Tl trihydrides, which have recently been synthesized in the gas phase but despite early claims by Wiberg of their isolation (that could not be reproduced), it would appear that solid phase isolation of InH 3 and TlH 3 is unlikely. Nevertheless, the heavier trihydrides are included for comparison in the present study, and may potentially be isolatable as adducts with NHCs with the reaction of lithium complexes such as LiInH 4 , which Jones and co‐workers employed in the isolation of an NHC–InH 3 adduct …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…There remains significant debate around the stability of In and Tl trihydrides, which have recently been synthesized in the gas phase but despite early claims by Wiberg of their isolation (that could not be reproduced), it would appear that solid phase isolation of InH 3 and TlH 3 is unlikely. Nevertheless, the heavier trihydrides are included for comparison in the present study, and may potentially be isolatable as adducts with NHCs with the reaction of lithium complexes such as LiInH 4 , which Jones and co‐workers employed in the isolation of an NHC–InH 3 adduct …”
Section: Resultsmentioning
confidence: 98%
“…Numerous studies have also demonstrated that group 13 hydrides can be stabilized by NHCs, including the boron mediated reactions reported by Schaefer, Schleyer and Robinson to stabilize both a B=B double bond and a bridged BH 2 complex . Extensive work has been carried out by Jones and co‐workers in the stabilization of the majority of the group 13 hydrides including Al, Ga, In and Tl . Other notable outcomes include the AlH 3 adduct of NHC Mes reported by Cole and co‐workers, the AlMe 3 adduct of NHC t Bu by Dagorne, and the gallium‐chloride species isolated by Nolan …”
Section: Resultsmentioning
confidence: 99%
“…[15] The crystal structure of the cationic component of 8 is shown in Figure 7 . [16] Interestingly, both the terminal and bridging InϪCl bonds (2.567 Å av. and 2.872 Å av., respectively) are considerably longer than the norms for such bonds (2.45 and 2.59 Å ) [17] and indeed, the bridging Cl Ϫ ligand can be thought of as only having an interaction (2) 2.592(2), In(1)ϪO(1) 2.174 (7), In(1)ϪC(1) 2.233 (7), In(1)ϪC (8) 2.235 (7), In(2)ϪCl(1) 2.921(2), In(2)ϪCl(3) 2.542(2), In (2)ϪO (1) 2.172 (7), In(2)ϪC (15) 2.221 (7), In(2)ϪC (22) 2.218(8); In(1)ϪO(1)ϪIn (2) 113.6(3), In(1)ϪCl(1)ϪIn (2) 78.54(5), Cl (2)ϪIn (1)ϪC(1) 94.64(18), Cl(2)ϪIn(1)ϪC (8) 91.51(19), C(1)ϪIn(1)ϪC (8) 109.2(3), Cl(1)ϪIn(1)ϪCl (2) 172.16 (6) (2)ϪCl(1) 81.1(2), Cl(1)ϪIn (2)ϪCl (3) 173.72 (7), N(1)ϪC(1)ϪN (2) 105.5 (6), N(3)ϪC (8)ϪN (4) 105.6(6), N(5)ϪC (15)ϪN (6) 103.9 (6), N(7)ϪC(22)ϪN (8) 104.9(6) with the indium centres.…”
Section: Structural Studiesmentioning
confidence: 99%
“…[4] Most success has been had with highly nucleophilic N-heterocyclic carbenes (NHCs), which form strong C À In dative bonds and discourage the formation of intermolecular In-H-In bridges by providing a degree of steric shielding to the InH 3 fragment. [5] A number of alkyl, halogen, phosphido and gallyl indium hydride complexes [4,6] have also been prepared and are finding applications in inorganic [4] and organic synthesis. [7] For these applications to expand, greater control over the thermal stability of indium hydride complexes is required.…”
Section: In Memory Of Colin Eabornmentioning
confidence: 99%